2016
DOI: 10.21315/mjde2016.18.1.6
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Information and Communication Technology in English Learning: Indigenous Students' Perspectives

Abstract: The increasing dependence of people on technology nowadays is evident through the transformation of various sectors, placing Information and Communication Technology (ICT) as an enabler in enhancing human capabilities and participations as a member of society. Policymakers and educators agreed that ICT is a supreme factor in leveraging positive effects on the students' achievements at large. Although myriad of studies have focused on ICT integration in education of students from the rural communities, the ICT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
3
1
Order By: Relevance
“…Of the evaluated indicators of the TIC competences dimension, it can be denoted that there is a high level of computers, but a moderated internet management, which agrees with what was mentioned by [17], who determined that by factors of lack of material the improvement in the use of these is minor but in the same way there is an interest in learning to use the internet correctly. Finally, the Learning indicator obtained an average of 2.5, indicating the low level of learning in terms of ICT, which contrasts with that established by [18], who mention that access to the Internet allows to facilitate the learning of the management of these tools, due to the good adaptation of the indigenous communities to the use of the internet and their low level of learning.…”
Section: Resultscontrasting
confidence: 58%
“…Of the evaluated indicators of the TIC competences dimension, it can be denoted that there is a high level of computers, but a moderated internet management, which agrees with what was mentioned by [17], who determined that by factors of lack of material the improvement in the use of these is minor but in the same way there is an interest in learning to use the internet correctly. Finally, the Learning indicator obtained an average of 2.5, indicating the low level of learning in terms of ICT, which contrasts with that established by [18], who mention that access to the Internet allows to facilitate the learning of the management of these tools, due to the good adaptation of the indigenous communities to the use of the internet and their low level of learning.…”
Section: Resultscontrasting
confidence: 58%
“…However, global distribution of ICTs in the most Indigenous villages is not as advanced as in the urban area (Bala & Tan, 2021). Their community's geographic location restricts their access to ICT and worsens the digital gap, which slows the expansion of ICT in education within the Indigenous community (Luaran et al, 2016). As they live and work in specific locations and speak only their own culture's language, Indigenous students who use ICT sparingly have difficulty understanding and using instructional software that is often produced in English and is text-heavy (Kenrick & Lewis, 2004;Stephens et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The use of ICT among IPs has been investigated in multiple contexts [9], [10], [11], [13], while the development, considerations, and integration of culturally-relevant teaching techniques and pedagogies for learners from diverse backgrounds in classroom settings were specifically explored in various studies as well [2], [4], [11], [18], [19], [20]. For one, Byrd [2] explored the effectiveness of culturally relevant teaching methods towards improved learning outcomes, increased engagement, and minimized achievement gaps among learners.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Byrd [2] analyzed the learners' perspectives and concluded that academic outcomes are closely related to culturally relevant pedagogies [19]. The use of such pedagogies has proven to have a positive impact on learners [4], [11], [18], [20]. Moreover, the addition of existing knowledge from the community has manifested benefits for socially diverse learners [18].…”
Section: Introductionmentioning
confidence: 99%